2020
DOI: 10.1186/s12870-020-02735-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Transcriptome analysis reveals lignocellulose synthesis regulation in elephant grass (Pennisetum purpureum Schum)

Abstract: Background The characteristics of elephant grass, especially its stem lignocellulose, are of great significance for its quality as feed or other industrial raw materials. However, the research on lignocellulose biosynthesis pathway and key genes is limited because the genome of elephant grass has not been deciphered. Results In this study, RNA sequencing (RNA-seq) combined with lignocellulose content analysis and cell wall morphology observation using elephant grass stems from different development stages as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In wheat, maize, and rice, 14, 10, and 11 CESAs members have identified, respectively [ 37 , 54 , 55 , 56 ]. In grasses, in Panicum virgatum 14 CESA genes have been reported [ 56 ], while an RNA-seq analysis revealed 27 CESA genes expressed during stem development of Pennisetum purpureum [ 57 ]. Here, we retrieved only six CESA orthologous in A. tequilana , which is quite comparable with that found in the hybrid H11648 (five CESA genes) [ 17 ] but contrasts with that reported recently in A. fourcroydes , A. sisalana , and H11648 (14 CESA genes) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, maize, and rice, 14, 10, and 11 CESAs members have identified, respectively [ 37 , 54 , 55 , 56 ]. In grasses, in Panicum virgatum 14 CESA genes have been reported [ 56 ], while an RNA-seq analysis revealed 27 CESA genes expressed during stem development of Pennisetum purpureum [ 57 ]. Here, we retrieved only six CESA orthologous in A. tequilana , which is quite comparable with that found in the hybrid H11648 (five CESA genes) [ 17 ] but contrasts with that reported recently in A. fourcroydes , A. sisalana , and H11648 (14 CESA genes) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few tissue-specific transcriptome works on forage grasses have been done to identify candidate genes involved in tissue development and forage quality improvement. Research on elephant grass ( Pennisetum purpureum ) stem lignocellulose identified 3,852 DEGs, and screened 43 candidate genes involved in lignocellulose biosynthesis, which might promote the development of high-quality elephant grass varieties [ 7 ]. We found 1,570 stem-specific genes, among which those significantly enriched in the phenylpropanoid biosynthesis pathway might affect the feed value of B. catharticus , as phenylpropanoid metabolism is a major pathway of lignocellulose biosynthesis [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on elephant grass ( Pennisetum purpureum ) stem lignocellulose identified 3,852 DEGs, and screened 43 candidate genes involved in lignocellulose biosynthesis, which might promote the development of high-quality elephant grass varieties [ 7 ]. We found 1,570 stem-specific genes, among which those significantly enriched in the phenylpropanoid biosynthesis pathway might affect the feed value of B. catharticus , as phenylpropanoid metabolism is a major pathway of lignocellulose biosynthesis [ 7 , 25 ]. While we identified 3,030 leaf-specific genes mainly related to the photosynthetic pathways, which might be of benefit in the improvement of leaf photosynthetic efficiency and biomass parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, RNA-seq technology can be applied to the study of various traits in various plants, such as using RNA-seq to study the identification of Lycium chinense biosynthesis genes and the accumulation of phenylpropanoids [ 19 ]. RNA-seq was used to investigate the protection of anthocyanins against Begonia semperflorens at low temperatures [ 20 ], and RNA-seq was used to study the regulation of elephant grass lignin synthesis [ 21 ]. In this study, Chinese cabbage was studied at a low temperature by the RNA-seq method, and the lignin synthesis pathway was further explored at a low temperature.…”
Section: Introductionmentioning
confidence: 99%